(untitled) (Archaeologia Adriatica, 2008)
In analyzing the geometric and figural patterns of all known mosaics from urban Issa, the conclusion is reached that mosaic production on the eastern Adriatic coast existed as early as the Hellenistic period. The emblem preserved to the present day, discovered at the beginning of the 20th century in the floor of the unfortunately destroyed Hellenistic mausoleum, belongs in terms of its stylistic and artistic characteristics to the Hellenistic mosaic tradition of Sicily and the Italian mainland, and the author considers it most likely to be an import, dating it to the transition from the 2nd to the 1st centuries BC. Numerous floor mosaics from the transition from the 1st to the 2nd centuries AD have been preserved in the framework of the large Roman urban thermal baths. The dominant Roman severity and simplicity of geometric forms was enriched by a playful figure of a dolphin as a connection to the early Hellenistic mosaics. A reflection of this earliest mosaic production is clearly apparent in the selection of the predominant motifs of meanders and swastikas. The mosaics of the Issa thermae, as a uniform artistic unit preserved in the original architectural framework, are a reflection of a highly active production of mosaics, based on a strong Hellenistic tradition and the increasingly professional local production, which followed the usual repertory of Roman models of the 1st and 2nd centuries. By viewing this group of mosaics created in the immediate vicinity of the capital city of Salona, it is possible to perceive the outlines of the creation and early activities of the Salonitan school of mosaics, which certainly in its very beginnings must have relied on the Hellenistic traditions of Pharos, and most definitely on those of Issa.